Positive psychology interventions and L2 speaking: a PERMA-based study on IELTS proficiency - Soheila Esmaeilee; Amir Mahdavi-Zafarghandi; Masoud Khalili Sabet; Jaleh Hassaskhah (Language Testing in Asia)
Abstract Positive psychology interventions have gained increasing attention for their potential to enhance academic performance, yet their impact on second language acquisition, mainly speaking proficiency, remains underexplored. This study investigates the effects of a Positive Psychology intervention program, grounded in Seligman’s (2011) PERMA model—Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment—on improving the speaking skills of English as a Foreign Language (EFL) learners. The present study involved a group of 59 female Iranian EFL learners, reflecting cultural norms and the single-sex context of their educational environment. These participants, aged 15–17, who had been studying English for five years, were divided into an experimental group (N = 30) and a control group (N = 29), using a convenience sampling method. The experimental group engaged in PERMA-based activities focusing on positive emotions, engagement, relationships, meaning, and accomplishment, while the control group received standard speaking instruction. Both groups participated in a curriculum integrating speaking, listening, grammar, reading, and writing through four weekly two-hour sessions. Using a one-way analysis of covariance (ANCOVA), the results indicated the effectiveness of the intervention, highlighting strategies to help learners address specific challenges. The research explores the theoretical and practical implications of incorporating positive psychological interventions in foreign language teaching, suggesting that such approaches can enhance learners’ skills and contribute to better academic outcomes.